Replication data for: Possessive constructions in North Saami prose - Antonsen, Lene; Janda, Laura A. (DataverseNO, 2015)
We present an analysis of nearly 4K examples of possessive constructions extracted from nearly 0.7M words of North Saami prose representing works of authors born in three time periods (1870-1927, 1947-1957, 1972-1983), plus a recent (1998) translation of the New Testament. The examples document an ongoing language change in which the possessive suffix attached to a noun (“SOG”) is being replaced by the genitive reflexive pronoun preceding the noun (“ieža-”). All examples are hand tagged for the two constructions, SOG vs. ieža-, plus a host of variables including the case and semantic class of the possessum and possessor, the person and number of the possessor, the source of the example, and the generation and geographical location of the author. In addition to anaphoric, endophoric, and exophoric reference previously described, we discover a generic type of reference. We track the progress of the language change across generations and find Johan Turi exceptional because he used ieža- more than his contemporaries. We focus particularly on examples of double marking of possession, and on examples where the number of the possessive construction does not match the possessor, and on the case and semantic class of possessor and possessum. It appears that semantics play a greater role in the choice of possessive constructions for the middle and young er generations than for the older generation. We hypothesize that the greater morphological complexity of the SOG construction is a language-internal factor that has contributed to its decline.